JUSTICE IN THE DISTRIBUTION OF MARITAL PROPERTY UPON THE DISSOLUTION OF MARRIAGE - Handayani, Septi Audina; Putra, Moody R. Syailendra (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
In marriage, there is joint property that is included in the marital property owned by the couple in the marriage. Indonesia regulates this marital property in several regulations, one of which is Law Number 1 of 1974 concerning Marriage. Joint property is property acquired during marriage by the husband and wife. The existence of property in marriage often becomes a problem when the couple divorces. Divorce can be the beginning of problems regarding property in marriage. Regarding the division of property, it cannot be done arbitrarily, but must be emphasized in terms of fairness. In this regard, the Marriage Law gives freedom to every divorced couple who wish to divide their joint property according to their respective laws. In the provisions of the Marriage Law, joint property, personal property, and earned property are types of property in marriage. This study aims to analyze the legal provisions on joint property in the Marriage Law and the Compilation of Islamic Law, as well as the division of property for divorced couples, which must be based on fairness. This study uses a normative juridical research method through a legislative approach based on written laws in Indonesia as the legal material used.